THE PREVALENCE OF URINARY TRACT INFECTIONS AND THE AGENTS RESPONSIBLE FOR THEM IN PREGNANT WOMEN IN THE PROVINCE OF KARBALA - Muhanna Redha, Huda; Jawad Hussein , Basim; Abbas Sadiq Alqaisi, Ali; Kadhim Hamadan, Wisam; Hadi Obiad , Zahraa; Jalal Abood , Ali (Journal of Medical Genetics and Clinical Biology, 2025)
Objective: This study aimed to determine the prevalence of urinary tract infections (UTIs) and identify the uropathogens present in pregnant women. Methods: A total of 417 midstream urine samples were collected and examined between December 2021 and August 2022. The diagnosis of UTI was established when a urinary tract pathogen exhibited growth of at least 10510^5105 CFU/ml in culture. Isolated microorganisms were identified using biochemical assays. Results: The findings revealed that 49.4% of the pregnant women had a UTI. Among the isolated organisms, E. coli was the most prevalent (56.79%), followed by Proteus sp. (5.8%), Pseudomonas sp. (6.3%), and Klebsiella sp. (19.9%). Novelty: This study provides updated insights into the prevalence and microbial profile of UTIs among pregnant women, highlighting the dominance of E. coli as the leading uropathogen during pregnancy.